Author Correction: Long-QT founder variant T309I-Kv7.1 with dominant negative pattern may predispose delayed afterdepolarizations under β-adrenergic stimulation - Iva Synková; Markéta Bébarová; Irena Andršová; Larisa Chmelikova; Olga Švecová; Jan Hošek; Michal Pásek; Pavel Vít; Iveta Valášková; Renata Gaillyová; Rostislav Navrátil; Tomáš Novotný (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.